2005
DOI: 10.1074/jbc.m413482200
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 Promotes Neurite Outgrowth in a Phosphorylation-dependent Manner

Abstract: In eukaryotic cells IQGAP1 binds to and alters the function of several proteins, including actin, E-cadherin, ␤-catenin, Cdc42, and Rac1. Yeast IQGAP1 homologues have an important role in cytoskeletal organization, suggesting that modulation of the cytoskeleton is a fundamental role of IQGAP1. Phosphorylation is a common mechanism by which cells regulate protein function. Here we demonstrate that endogenous IQGAP1 is highly phosphorylated in MCF-7 human breast epithelial cells. Moreover, incubation of cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 49 publications
3
87
0
Order By: Relevance
“…This is not surprising as IQGAP1 is a significant modulator of cytoskeletal architecture across a wide spectrum of organisms, ranging from yeast to Xenopus to mammals [15]. IQGAP1 influences numerous cell functions, including actin polymerization, microtubule function, cell-cell adhesion and neurite outgrowth [3,15,16,35]. These effects are mediated by a direct interaction between IQGAP1 and multiple-binding proteins [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as IQGAP1 is a significant modulator of cytoskeletal architecture across a wide spectrum of organisms, ranging from yeast to Xenopus to mammals [15]. IQGAP1 influences numerous cell functions, including actin polymerization, microtubule function, cell-cell adhesion and neurite outgrowth [3,15,16,35]. These effects are mediated by a direct interaction between IQGAP1 and multiple-binding proteins [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that IQGAP1 is phosphorylated in cells in a PKC⑀-dependent manner at Ser 1443 in response to phorbol ester treatment (28,37). It seems reasonable, therefore, to hypothesize that IQGAP1 can be phosphorylated on Ser 1443 in response to EGF-stimulated activation of EGFR.…”
Section: Iqgap1 and Egfr Interact In Cells-iqgap1mentioning
confidence: 99%
“…IQGAP1-IQ (amino acids 717-916) and IQGAP1⌬IQ (full length minus amino acids 746 -860) have been described previously (27). IQGAP1-SAA (serines 1441 and 1443 mutated to alanine) and IQGAP1-SED (serines 1441 and 1443 mutated to glutamic acid and aspartic acid, respectively), were generated as Myc-tagged constructs and have been described previously (28). Glutathione S-transferase-tagged full-length IQGAP1 fusion protein (GST-IQGAP1) has been described previously (26).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations